Paranoia [large type] - Patterson, James, 1947-; Born, James O. (Patterson, James, 1947- Detective Michael Bennett thriller., 2025)
"At every death scene, Bennett says a prayer over the victim. But recently, too many of departed have been fellow cops. 'I want you to look at these deaths on special assignment,' NYPD Inspector Celeste Cantor says. 'Report only to me.' Bennett excels as a solo investigator. But he's chasing a killer who feeds on isolation--and paranoia"--